Optimization of processing parameters for extraction of amylase enzyme from dragon (Hylocereus polyrhizus) peel using response surface methodology - Amid, Mehrnoush; Abd Manap, Mohd Yazid; Ahmad Zohdi, Nor Khanani (Hindawi Publishing Corporation, 2014)
The main goal of this study was to investigate the effect of extraction conditions on the enzymatic properties of thermoacidic amylase enzyme derived from dragon peel. The studied extraction variables were the buffer-to-sample (B/S) ratio (1: 2 to 1: 6, w/w), temperature (-18°C to 25°), mixing time (60 to 180 seconds), and the pH of the buffer (2.0 to 8.0). The results indicate that the enzyme extraction conditions exhibited the least significant (P < 0.05) effect on temperature stability. Conversely, the extraction conditions had the most significant (P < 0.05) effect on the specific activity and pH stability. The results also reveal that the main effect of the B/S ratio, followed by its interaction with the pH of the buffer, was significant (P < 0.05) among most of the response variables studied. The optimum extraction condition caused the amylase to achieve high enzyme activity (648.4 U), specific activity (14.2 U/mg), temperature stability (88.4%), pH stability (85.2%), surfactant agent stability (87.2%), and storage stability (90.3%).